Implementing citizenship education in forming mutual character in elementary school - Yustisi, Mia Dara; Mulyono, Ana; Musafir, Musafir (Nashir Al-Kutub Indonesia, 2023)
The research aimed to determine how citizenship education instilled the character of mutual cooperation in elementary school. This qualitative study, employing a descriptive approach, sought to explore how citizenship education was integrated into the development of mutual cooperation among students. Conducted at one of the elementary school in North Lombok, Indonesia. The research involved the principal, citizenship education teacher, and class IV students as its subjects. The researcher served as the key instrument, supported by interviews, documentation, and observation tools. Findings revealed that teachers consistently applied citizenship education during the learning process. Topics such as rights, obligations, and mutual cooperation were taught, though students often struggled to comprehend the material and hesitated to ask questions for clarification. The discrepancy between student activities at school and at home posed challenges for teachers. Additionally, the lack of textbooks forced educators to rely on cellphones for instructional materials. Students found citizenship education both challenging and inconsistently engaging. To address these issues, teachers and school principals implemented habituation strategies. These strategies aimed to integrate citizenship education into daily routines, fostering mutual cooperation, where students actively participated in various activities.